2015
DOI: 10.1088/0004-637x/815/1/73
|View full text |Cite
|
Sign up to set email alerts
|

Multithermal Representation of the Kappa-Distribution of Solar Flare Electrons and Application to Simultaneous X-Ray and Euv Observations

Abstract: Acceleration of particles and plasma heating is one of the fundamental problems in solar flare physics. An accurate determination of the spectrum of flare energized electrons over a broad energy range is crucial for our understanding of aspects such as the acceleration mechanism and the total flare energy. Recent years have seen a growing interest in the kappa-distribution as representation of the total spectrum of flare accelerated electrons. In this work we present the kappa-distribution as a differential em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
(35 reference statements)
1
27
0
Order By: Relevance
“…In addition to that, Battaglia, Motorina, and Kontar (2015) found that fitting the combined RHESSI and AIA data together can be done by using a two-component ξ κ (T ) function, consisting of ξ These analyses show that taking account of the larger observed energy range provides tighter constraints on the mean electron flux spectrum present in the flare plasma. Additionally, approximating only a limited energy range (e.g., only RHESSI observations above several tens of keV) could in principle lead to misleading results on the nature of the non-thermal component present in the plasma.…”
Section: Mean Electron Fluxes From Rhessi and Aia Observationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to that, Battaglia, Motorina, and Kontar (2015) found that fitting the combined RHESSI and AIA data together can be done by using a two-component ξ κ (T ) function, consisting of ξ These analyses show that taking account of the larger observed energy range provides tighter constraints on the mean electron flux spectrum present in the flare plasma. Additionally, approximating only a limited energy range (e.g., only RHESSI observations above several tens of keV) could in principle lead to misleading results on the nature of the non-thermal component present in the plasma.…”
Section: Mean Electron Fluxes From Rhessi and Aia Observationsmentioning
confidence: 96%
“…It consist of two components, ξ hot (T ) and ξ cold (T ), shown in blue and purple, respectively. From Battaglia, Motorina, and Kontar (2015), c AAS. Reproduced with permission.…”
Section: Mean Electron Fluxes From Rhessi and Aia Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this method, the data from the two instruments are treated as one data set and forward fitted with one model distribution. As shown by Battaglia et al (2015), this approach leads to a better constraint of the low-energy electrons, resulting in up to a factor of ∼ 30 lower total energy content of the electron distribution compared with traditional X-ray spectroscopy. Using these combined X-ray-EUV diagnostics, we can characterise the electron distribution function in the coronal regions of magnetic reconnection outflow during solar flares.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the Maxwellian distribution, the n-and kappa distributions represent two antipodes, the n-distribution function has a steeper (softer) energy tail than the Maxwellian distribution, while the kappa distribution has a harder energy tail. Both distributions are used to explain soft X-ray observations of solar flares, but in different cases (Kulinová et al 2011;Battaglia et al 2015). Leroy & Mangeney (1984) and Wu (1984) pointed out that nearly perpendicular collisionless shock waves are capable of accelerating electrons.…”
Section: Introductionmentioning
confidence: 99%